Rancang Bangun Multimedia Pembelajaran Berbasis WEB Konsep Kegiatan Ekonomi Pembelajaran IPS Kelas V SD - Linda Puspita Sari; Tin Rustini; Dinie Anggraeni Dewi (Edumaspul: Jurnal Pendidikan, 2021)
The results of field studies that have been carried out at one of the state elementary schools in the Rancaekek area, Bandung, show that the use of learning media is very minimal due to the limited ability of teachers to create and utilize existing technology, especially digital technology for creative and innovative learning media, so students tend to be given assignments through theme book during social studies learning. Therefore, this study aims to create interesting multimedia learning as one of the uses of digital technology for elementary students in the form of web-based learning multimedia concepts of social studies learning economic activities. Besides aiming to create or design, it also aims to test and get responses from users of the designed multimedia. The research design used the Design and Development (D&D) research method or design and development. This web-based learning multimedia development procedure uses the ADDIE model (analyze, design, development, implement, and evaluate). The result of this development is to produce a product in the form of web-based multimedia learning the concept of economic activity for class V social studies learning. In addition to producing products, the results of the feasibility test of experts, namely media experts received 92.90% interpretation, and 96.40% from material experts. In addition, the user's assessment response got positive results with the percentage of 98.40% from teachers, and 89.20% from students. So that it can be categorized into a "Very Good" value interval. Web-based learning multimedia products that are recommended for use by parents in social studies learning.